Bimbingan Kelompok Teknik Bermain Peran untuk Meningkatkan Komunikasi Interpersonal Siswa Kelas XI IIS 4 Di SMA Antartika Sidoarjo - Bunga Desining Ramadhanti (Jurnal Syntax Transformation, 2021)
Interpersonal communication is communication between two or more people, face-to-face. The delivery of this message through words, gestures, and facial expressions. The aim of this research is to find out Group Role-Playing Guidance can improve students' interpersonal communication. This research is a type of quantitative research using pre-experimental research design methods using one group pre-test-post-test design. In this study has two variables that consist of bound variables or variables X (Interpersonal Communication) and also free variables or variables Y (Role Playing group guidance). The population in this study was high school students. The sample in the study was 5 students who had the lowest interpersonal communication scores. For this study using the Wilcoxon test assisted by SPSS for windows version 24.0. It can be concluded in this study that Ha is accepted. This means that there is a difference between students' interpersonal communication for pre-test and post-test, so it can be concluded that Role-Playing Engineering Group Guidance can Improve Interpersonal Communication Of Class XI IIS 4 Students at Sidoarjo Antarctic High School